Analisis Efektifitas Kebijakan Pengaduan Publik dalam Pelayanan Adminitrasi Publik - Bunda, Maria Rosalia; Tjenreng, Muhammad Baharuddin Zubakhrum (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This study aims to analyze the effectiveness of public complaint policies in improving the quality of public administration services. The research uses a qualitative approach with a descriptive method. Data were collected through interviews, document studies, and direct observation. The results show that public complaint policies play an important role in enhancing public participation and government accountability. However, the effectiveness of these policies still faces challenges, such as the lack of responsiveness from officers and limitations in technological infrastructure. This study recommends improving training for officers, optimizing information technology, and raising public awareness of complaint mechanisms.